Circulating S100A8/A9 Levels Reflect Intraocular Inflammation in Uveitis Patients. (2nd January 2020) - Wang, Yu-Qin; Dai, Xiao-Dan; Ran, Yun; Cao, Ying; Lan, Chun-Lin; Guan, Ji-Tian; Liu, Chang; Yang, Feng-Mei; Gan, Yi-Jing; Liu, Bai-Jing; Fang, Ai-Wu; Lin, Dan; et al.
ABSTRACT: Purpose: To investigate whether there is an association between circulating S100A8/A9 levels and uveitis activity. Methods: A total of 549 plasma samples were collected from uveitis patients and non-uveitic controls. Results: S100A8/A9 plasma levels were elevated in uveitis patients compared to non-uveitic controls ( P  < 0.001). S100A8/A9 plasma levels in patients with active acute anterior uveitis (AAU) were significantly elevated and remarkably decreased in parallel with the severity of intraocular inflammation after corticosteroid treatment ( P  < 0.001). S100A8/A9 plasma levels were also higher in AAU patients with ankylosing spondylitis (AS) than in patients without AS ( P  = 0.02). S100A8/A9 plasma levels were significantly increased in uveitis patients with elevated C-reactive protein (CRP, P  = 0.004) or erythrocyte sedimentation rates (ESR, P  = 0.049) levels compared to uveitis patients with normal CRP or ESR values. Conclusion: Circulating S100A8/A9 might be a useful biomarker for the measurement of intraocular inflammation.